2013
DOI: 10.2478/stcb-2013-0002
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Customer Satisfaction in Fast Food Industry A Study of Fast Food Restaurants Peshawar Pakistan

Abstract: This research is focused to find what are the key success factors for fast food industry in region of Peshawar Pakistan. Fast food concepts developed very rapidly in last few years in Peshawar region. The failure or success of a fast food industry based on some factors like Promotion, Service quality, Customer expectations, Brand, Physical Environment, Price, and Taste of the product. To find which of these factors has greater influence on consumer satisfaction, four fast food restaurants customers were target… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
14
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 7 publications
2
14
0
3
Order By: Relevance
“…Potential customers are easily impacted by negative WOM and they may draw potential customers away from the service provider (Wilson et al , 2012). With respect to the fast food industry, Khan et al (2013) pointed out that all the determinants of customer satisfaction fell into one of seven categories which were physical environment, service quality, brand, promotion, customer expectations, price and taste of food. Their results concluded that the main factors for customer satisfaction were service quality and brand.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…Potential customers are easily impacted by negative WOM and they may draw potential customers away from the service provider (Wilson et al , 2012). With respect to the fast food industry, Khan et al (2013) pointed out that all the determinants of customer satisfaction fell into one of seven categories which were physical environment, service quality, brand, promotion, customer expectations, price and taste of food. Their results concluded that the main factors for customer satisfaction were service quality and brand.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Based on the paradigm of Wilson et al (2012), Figure 1 illustrates the relationship between service quality and customer satisfaction. In terms of the fast food industry, according to Heung et al (2000), Jain and Gupta (2004), Qin and Prybutok (2009), and Khan et al (2013), price, product quality and service quality relate directly to customer satisfaction; however, comparing product quality and price, the perceived service quality factor plays the most important role on overall satisfaction.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…They also pointed out that service encounter performance has a direct impact on customer satisfaction. Khan et al (2013) found that brand and service quality are key factors that affect satisfaction in fast-food industry. In their study, Nguyen et al (2018) identified that physical attributes of service quality (tangible) are key to customer satisfaction.…”
Section: Restaurant Customer Satisfactionmentioning
confidence: 99%
“…The drivers of customer satisfaction have been identified in the research literature and include price, employee courtesy, timely service, competence of staff, food quality, accessibility, and cleanliness (Gilbert et al, 2004;Khan et al, 2013;Puri and Kumar, 2014). In the current research, we conceptualize and operationalize these drivers as the marketing mix, also known as the 7 Ps of marketing, which include price, product, place, promotion, packaging, positioning, and people.…”
Section: Rq1: How Does the Marketing MIX Affect Customer Satisfactionmentioning
confidence: 99%